Physical Properties Of Estrual Mucus In Gir Cows With Reference To Their Body Condition Score And Fertility - Gohel, M.M.; Kavani, F.S.; Hadiya , K.K. (Indian Journal of Veterinary Sciences and Biotechnology, 2012)
Fifty Gir cows (10=normal cyclic, 20=repeat breeders and 20=hormonally-CIDR induced estrus) were used to determine physical properties of estrual cervico-vaginal mucus (CVM) collected 5 to 30 minutes before the first AI. In normal cyclic cows, clean and thin CVM with higher spinnbarkeit value (14.40±0.30 cm) showing typical fern pattern (80 %) was observed to provide favourable environment for conception. In induced estrus cows, clean or turbid and thin or thick mucus with atypical fern pattern was observed to favour conception. Among all the groups, viz., normal cyclic, repeat breeders and induced estrus, non-significantly higher mean pH of CVM was observed in non-conceived as compared to conceived cows (7.40±0.10, 7.62±0.15 and 7.28±0.07 vs 7.11±0.0, 7.54±0.15 and 7.34±0.08). The physical properties of CVM in general were independent of conceived and non-conceived status in normal cyclic, repeat breeder and induced estrus cows. The findings revealed the higher mean value of body condition score in repeat breeder (3.27±0.07) as compared to induced estrus (3.00±0.07) and normal cyclic cows (2.90±0.08). The typical fern pattern was observed more in normal cyclic and induced estrus cows with 3.0 BCS (Body Conditon Score) as compared to repeat breeder cows with similar BCS whereas, the atypical fern pattern was observed more in repeat breeder with the 3.5 BCS as compared to induced estrus cows and normal cyclic cows with the similar BCS. The turbid and dirty colour of CVM was observed more in repeat breeder cows with the 3.5 BCS.